Amassing of heavy metals in soils, vegetables and crop plants irrigated with wastewater: Health risk assessment of heavy metals in Dera Ghazi Khan, Punjab, Pakistan - Atta, Muhammad Imran; Zehra, Syeda Sadaf; Dai, Dong-Qin; Ali, Habib; Naveed, Khalid; Ali, Iftikhar; Sarwar, Muhammad; Ali, Basharat; Iqbal, Rashid; Bawazeer, Sami; Abdel-Hameed, Usama K.; Ali, Iftikhar (Frontiers in Plant Science, 2023)
An unremitting boost of heavy metals into the environment from wastewater irrigation has become a global issue. These heavy metals enter the food chain and pose health assumptions to consumers upon utilization. In the present study, an investigation has been conducted to determine metal concentrations in the wastewater, soil, and different plant species. For wastewater samples, pH, total dissolved solids (TDS), electrical conductivity (EC), and selected heavy metals such as Al, As, Cr, Cu, Fe, Mn, Pb, Zn, and Ni were determined. The mean values of heavy metals in the soil samples were within the WHO/FAO safe limit, while Cr and Pb were the most frequent (100%) among the metals. However, differentiating the sites, the concentration of Cr and Cu, Ni, and Fe were elevated. The metal transfer was highly effective from soil to the growing plants i.e. brinjal, red corn, wheat, tomato, and spinach than other plant species. Among the metals, Cr, Ni, Mn, and Pb in plant samples were exceeding the WHO/FAO safe limit. Health risk index (HRI) have revealed the possible potential risk of heavy metal contaminated plant species in the order of spinach (6.4) > wheat (6.4) > brinjal (5.9) > tomato (4.7) > red corn (4.5) > apple gourd (4.3) > white corn (3.8) > cabbage (3.1) > luffa (2.9). Likewise, HRI of different metals was calculated as Cu (19.6) > Zn (17.9) > Cr (2.95) > Ni (0.85) > Mn (0.48) > Fe (0.15) > Cd (0.11) > Pb (0.05) > As (0.00001). The level of HRI through the use of dietary plants revealed an elevated risk level than the acceptable limit (HRI > 1) for Cu > Zn > Cr in adults. Our findings suggest that there would be a serious health risk to the consumers due to the consumption of these plant species being irrigated with the wastewater. Therefore, a strict regulatory mechanism is proposed for the safety of food plants in the study area including monitoring and recycling of crop plants, and building water treatment plants to remove pollutants and clean wastewater.